Pemanfaatan Video Streaming Pada Sistem Keamanan Rumah Dengan Menggunakan Mobile Devices - Mahatmaputra, Samuel (ComTech: Computer, Mathematics and Engineering Applications, 2010)
This research has been produced a function prototype of video streaming with JPEG/MJPEG picture quality in a residential security system using mobile device (cell phone). The security system is an early warning system which server will deliver text messaging to client if there is an event in the censor of home webcam to detect movement. The prototype is divided into two types, server and client. The client will be installed a mobile application that automatically activated if there is inbound message in specific port. Meanwhile, the application in user client is completed with functionality to visit particular webpage, one touch call to security phone numbers to do setting (previous research result). And, as the research objective this year, user will see the video streaming in a good quality from the object.